Anatomic Site–Specific Gonorrhea and Chlamydia Testing and Incidence Among People With HIV Engaged in Care at 4 US Clinical Centers, 2014–2018. (17th June 2022) - Menza, Timothy W; Berry, Stephen A; Dombrowski, Julie; Cachay, Edward; Crane, Heidi M; Kitahata, Mari M; Mayer, Kenneth H
Abstract: Background: The incidence of Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT) is increasing in the United States; however, there are limited data on anatomic site–specific GC/CT among people with HIV (PWH). Methods: We reviewed records of all PWH in care between January 1, 2014, and November 16, 2018, at 4 sites in the CFAR Network of Integrated Clinical Systems Cohort (CNICS; n = 8455). We calculated anatomic site–specific GC/CT testing and incidence rates and used Cox proportional hazards models modified for recurrent events to examine sociodemographic and clinical predictors of GC/CT testing and incidence at urogenital, rectal, and pharyngeal sites. We also calculated site-specific number needed to test (NNT) to detect a positive GC/CT test. Results: Of 8455 PWH, 2460 (29.1%) had at least yearly GC/CT testing at any anatomic site. The rates of urogenital, rectal, and pharyngeal GC were 1.7 (95% CI, 1.6–1.9), 3.2 (95% CI, 3.0–3.5), and 2.7 (95% CI, 2.5–2.9) infections per 100 person-years, respectively. The rates of urogenital, rectal, and pharyngeal CT were 1.9 (95% CI, 1.7–2.1), 4.3 (95% CI, 4.0–4.5), and 0.9 (95% CI, 0.8–1.0) infections per 100 person-years, respectively. PWH 16–39 years old experienced greater GC/CT rates at all anatomic sites, while men who have sex with men experienced greater rates of extragenital infections. NNTs for urogenital, rectal, and pharyngeal GC/CT were 20 (95% CI, 19–21), 5 (95% CI, 5–5), and 9 (95% CI, 8–9), respectively. Conclusions: Many PWH are not tested annually for GC/CT, and rates of GC/CT infection, particularly rates of extragenital infections, are high. We identified groups of PWH who may benefit from increased site-specific GC/CT testing.